Evidence in Civil Law - Latvia - Rozenfelds, Jānis (Law & Society, 2015)
The national report of civil procedure in Latvia is based on review of the Latvian Civil Procedure Law, court practice, feedback by the Ministry of Justice on cooperation with the EU states as well as with third countries in various matters of jurisdiction as well as on legal science. Civil procedure includes all legal principles like disposition, right to be present and to be heard, competition of parties in gaining all necessary evidence and similar concepts to be found in almost every modern civil procedure system. However, there are certain specific features due to which Latvian process stands out. For instance, there is still a system of legal presumptions which apparently is inherited from Roman law, yet still prescribed by the Latvian Civil law (Civil code). Also certain degree of formal attitude remains as a characteristic feature of the Latvian civil procedure.